Study of nanocluster-assembled ZnO thin films by nanocluster-beam deposition - Zhao, Zhiwei (2013)
Nanocluster-assembled ZnO thin films were obtained by nanocluster-beam deposition, in which nanoclusters were produced by a magnetron sputtering gas aggregation source. Two kinds of ZnO thin films were obtained using this method with the one grown under the on-line heating temperature of 700 °C, and the other grown without on-line heating. Film microstructure and optical properties are investigated by various diagnostic techniques. It was found that both of film microstructure of ZnO thin films keep wurtzite structure as that of ZnO bulk materials. The averaged particle size for the film grown without on-line heating is around 6 nm, which is a little lower than that grown with the on-line heating. It was also found that as increasing the wavelength, both of the absorbance spectra for the films decrease sharply near ultra-visible to extend slowly to the visible and infrared wavelength range. For the film grown without on-line heating, the bandgap energy was estimated to 3.77 eV, while for the film grown with on-line heating, the bandgap energy was redshift to 3.71 eV. Similar behavior was also found for PL spectra analysis, where PL spectrum exhibited a peak centered at 3.31 eV without on-line heating, while it redshift to 3.20 eV with on-line heating. The mechanisms behind these behaviors were presented in this article.